Brilliant Acceptance Factor Analysis for Students Stikom Surabaya Methods UTAUT - Dhayana, Dinda; Sunarto, Dewiyani; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Brillian is application hybrid learning in Stikom Surabaya who web-based from google apps. Brillian having some function, namely function download lecture learning, collection duty, learning online media, assessment, and measuring the degree in common duty. Brillian can be a excellence compete for Stikom Surabaya. To know factors anything that affects the Brillian to university students Stikom Surabaya on this research use the model the unified theory of acceptance and use of technology (UTAUT). In this study technique data collection to analyze method utaut uses the Structural Equation Model (SEM). Processing and reliability the validity and descriptive use application spss .The sampling done with the Stratified Random Sampling (SRS) the students Stikom Surabaya the 2011- 2015 of all the program study. In the research indicated that of factors affect the brilliant is performance expectancy, effort expectancy, social influence, and facilitating conditions, but more affect the brilliant is the variable social influence. On the analysis result of this explains that all variable influence in the Brillian the students Stikom Surabaya.A factor that is affecting is variable the social experience of moderation 18,129 and facilitatng conditions with moderation experience of 22,092.